Impact of Punishment and Discipline on Employee Performance - Sariyono, Nurul; Herlambang, Toni; Martini, Ni Nyoman Putu; Qomariah, Nurul (Budapest International Research and Critics University, 2024)
Employee performance is an important thing to get attention in every line of the organization. Performance is a benchmark for the success of an organization. As a public organization, it is also required to provide the best service by improving employee performance. This research was conducted in Mayang District, Jember Regency, targeting all local ASN. The purpose of the study was to examine the effect of sanctions and discipline on ASN performance. Using a quantitative research method based on the philosophy of positivism, from a population of 215 ASN, 123 representative samples were taken with the Slovin formula. Data analysis used descriptive analysis, validity tests and reliability tests of research data, and direct influence tests. The results of the study showed that partial sanctions did not have a positive and significant effect on ASN performance. Employee discipline has been shown to have a significant positive effect on performance.